Answer:
x = -8
Explanation:
Solve for x:
3 (x + 8) = 2 (3 x + 24)
Expand out terms of the left hand side:
3 x + 24 = 2 (3 x + 24)
Expand out terms of the right hand side:
3 x + 24 = 6 x + 48
Subtract 6 x from both sides:
(3 x - 6 x) + 24 = (6 x - 6 x) + 48
3 x - 6 x = -3 x:
-3 x + 24 = (6 x - 6 x) + 48
6 x - 6 x = 0:
24 - 3 x = 48
Subtract 24 from both sides:
(24 - 24) - 3 x = 48 - 24
24 - 24 = 0:
-3 x = 48 - 24
48 - 24 = 24:
-3 x = 24
Divide both sides of -3 x = 24 by -3:
(-3 x)/(-3) = 24/(-3)
(-3)/(-3) = 1:
x = 24/(-3)
The gcd of 24 and -3 is 3, so 24/(-3) = (3×8)/(3 (-1)) = 3/3×8/(-1) = 8/(-1):
x = 8/(-1)
Multiply numerator and denominator of 8/(-1) by -1:
Answer: x = -8